Lessons Learned from HIV Vaccine Clinical Efficacy Trials - A. Day, Tracey; G. Kublin, James (Current HIV Research, 2013)
The past few years have witnessed many promising advances in HIV prevention strategies involving preexposure prophylaxis approaches. Some may now wonder whether an HIV vaccine is still needed, and whether developing one is even possible. The partial efficacy reported in the RV144 trial and the encouraging results of the accompanying immune correlates analysis suggest that an effective HIV vaccine is achievable. These successes have provided a large impetus and guidance for conducting more HIV vaccine trials. A key lesson learned from RV144 is that assessment of HIV acquisition is now a feasible and valuable primary objective for HIV preventive vaccine trials. In this article we review how RV144 and other HIV vaccine efficacy trials have instructed the field and highlight some of the HIV vaccine concepts in clinical development. After a long and significant investment, HIV vaccine clinical research is paying off in the form of valuable lessons that, if applied effectively, will accelerate the path toward a safe and effective vaccine. Together with other HIV prevention approaches, preventive and therapeutic HIV vaccines will be invaluable tools in bringing the epidemic to an end.
Keywords: HIV vaccine trials network